(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
This article presents and analyzes the pedagogical theoretical information about aesthetic education, its content, the influence of aesthetic education on personality formation, and the formation of axiological views of students in the process of aesthetic education.